2011
DOI: 10.1111/j.1551-2916.2011.04990.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Plate‐LikeZrB2Grains

Abstract: Plate‐like ZrB2 grains were synthesized at 1550°C by in situ solid/liquid reaction using Zr and B powders mixed with transition metal (Mo, Nb, Ti, or W) and Si powder. The preferred growth direction of plate grains was along a‐ or b‐axis depending on the initial content of transition metal and silicon in the mixtures. The synthesis mechanism of plate‐like grain was possibly related to the catalysis of in situ formed silicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…It means that during the solidification process, owing to its hexagonal crystal structure, the ZrB 2 grains were prone to grow along the cooling front resulting in elongated grains along the c ‐axis. This result is different with the one reported by Hu et al where under homogeneous temperature conditions ZrB 2 grains grew along a ‐ and b ‐axes in the presence of liquid silicon. In addition, it is found that mainly β‐SiC could be detected in the composite.…”
Section: Resultscontrasting
confidence: 99%
“…It means that during the solidification process, owing to its hexagonal crystal structure, the ZrB 2 grains were prone to grow along the cooling front resulting in elongated grains along the c ‐axis. This result is different with the one reported by Hu et al where under homogeneous temperature conditions ZrB 2 grains grew along a ‐ and b ‐axes in the presence of liquid silicon. In addition, it is found that mainly β‐SiC could be detected in the composite.…”
Section: Resultscontrasting
confidence: 99%
“…The liquid phase formed by the solid solution of the transition metal silicides enhanced the grain growth of the ZrB 2 grains. The preferred growth direction of the ZrB 2 plate grains along the a, b ‐axis has also been confirmed in several systems with different initial contents of transition metal and silicon in the initial mixtures …”
Section: Resultsmentioning
confidence: 58%
“…At present, a variety of methods have been performed to synthesize M B 2 powders with special morphologies. For example, plate‐like ZrB 2 grains were synthesized by in situ solid/liquid reaction using Zr and B powders mixed with transition metal (Mo, Nb, Ti, or W) and Si powder . Hexagonal‐prism‐like or rod‐like ZrB 2 particles were synthesized by a sol‐gel route .…”
Section: Introductionmentioning
confidence: 99%